Application of whole-process nursing cooperation in dental implant surgery for patients with loss of teeth and insufficient bone mass (全程护理配合在牙缺失合并骨量不足患者牙种植术中的应用效果) - YANG Yi (杨怡); ZHEN Xiaodan (郑晓丹); HAN Qin (韩琴) (Journal of International Translational Medicine Limited, 2022)
Objective To explore the effect of whole-process nursing cooperation in dental implantation for patients with loss of teeth and insufficient bone mass. Methods A total of 70 patients who underwent dental implant surgery in the dental clinic from September 2020 to August 2021 were selected as the research objects, and divided into the control group and the observation group according to the random number method, with 35 cases in each group. The control group was given routine nursing intervention, while the observation group was given whole-process nursing cooperation. The compliance, nursing satisfaction and 6-month postoperative complication rates were compared between the two groups. Results The compliance of patients in the observation group (94. 28%) was higher than that in the control group (82. 86%), with a significant difference (P＜0. 05). The score of nursing satisfaction assessment in the observation group was higher than that in the control group (P＜0. 05). The 6-month postoperative complication rate in the observation group was lower than that of the control group (5. 71% vs. 22. 86%, P<0. 05). Conclusion During the perioperative period of implantation, the whole-process nursing cooperation and postoperative health education could improve patients' compliance and nursing satisfaction, and reduce the incidence of postoperative oral complications. (目的 探讨全程护理配合在牙缺失合并骨量不足患者行牙种植术中的应用效果。方法 选取2020年9月-2021年8月口腔门诊行牙种植手术的牙缺失合并骨量不足患者70名为研究对象, 按照随机数字法分为对照组和观察组, 各35例。对照组进行常规护理干预, 观察组在对照组基础上实施全程护理配合。比较两组患者依从性、护理满意度以及术后6个月并发症发生率。结果 观察组患者依从性良好率94. 29%(33/35), 高于对照组80. 00%(28/35), 差异有统计学意义(P＜0. 05); 观察组护理满意度高于对照组, 差异有统计学意义(P＜0. 05); 观察组术后6个月并发症发生率5. 71%(2/35), 低于对照组的22. 86%(8/35), 差异有统计学意义(P＜0. 05)。结论 种植围手术期开展全程精细护理配合, 可提高患者就诊依从性和护理满意度, 降低术后口腔并发症发生率。)